THE PROBLEM OF CREATIVITY: WITH WHAT IMAGES DO YOUNG PEOPLE COME UP? - Balciuniene, Rasa Balte; Seputis, Gintaras (PEOPLE: International Journal of Social Sciences, 2018)
The article is devoted to the problem of perception of television and media images and the youth creativity. The study conducted by G. Seputis on the applicants of art colleges is reviewed, the study’s sample consisted of 80 boys and girls at the age of 18. The aim of the study is to analyse what kind of images emerge creating the storyboard on neutral theme “silence”. We analysed popular media content during the years of kids’ formation and tried to benchmark obvious ones similarity with film — television images. It is concluded that the neutral theme “silence” leads to the use of negative images in the drawings. The method of comparative analysis of drawings and TV images was used. The article presents correlation between drawings and TV images and clearly confirms the youth's response to the neutral stimulus "silence" with the reproduction of negative media images. It is concluded that it is necessary to create educational programs for adolescents. The article discusses studies of psychologists lead to the conclusion that viewing TV does not always cause a positive effect. The authors emphasize a high degree of negative behavioural problems in Lithuanian youth is made apparent. The influence of information created with the help of media channels on the development of the creativity in children and adolescents is discussed. The authors invite to use educational methods aimed at developing creativity in youth.